Effects of organic micromolecules in bituminous coal on its microscopic pore characteristics. (15th February 2020) - Ji, Huaijun; Mao, Yingnan; Su, Hetao
Graphical abstract: With the dissolution of organic micromolecules, the micropores of low-metamorphic bituminous coal were connected for opening the pore throats, however, for high-metamorphic bituminous coal, the number of micropores increased because the more new micropores are formed for opening the closed pores. Highlights: The pores of CYM sample were expanded into larger pores after extraction. The new micropores of JM sample were formed after extraction. The organic micromolecules in coal reduced the pore connectivity. The occurrences of organic micromolecules in coal were discussed. Abstract: Studying complex pore structures is the key to understanding the mechanism of coalbed methane accumulation and transport in coal. Two bituminous coals were extracted at 50 °C and at atmospheric pressure by using a microwave-assisted method with tetrahydrofuran as the solvent. The pore structures of raw coals and their residues were separately tested with scanning electron microscopy, gas adsorption (N2 and CO2 ), and high-pressure mercury intrusion porosimetry. After extraction, the specific surface area decreased from 9.90171 to 6.74875 m 2 /g for the Xiashijie Coal Mine sample because of the reduction in the number of micropores, whereas it increased from 4.01743 to 8.5832 m 2 /g for the Qingdong Coal Mine sample because of the increase in the number of micropores. In low-metamorphic bituminous coals, the organic micromolecules mainly occur in macropores and a few micropores. As the organic micromolecules dissolved, the number of micropores decreased because some of them were connected to macropores by the opening pore throats. In contrast, in high-metamorphic bituminous coals, organic micromolecules mainly occur in micropores and defects of aromatic layers; as they dissolved, more new micropores were formed by opening of the closed pores that were blocked by the organic micromolecules. Therefore, the organic micromolecules have an important influence on coal pores and their connectivity. This research is of significance for understanding the relationship between coal composition and pore structure.